Ответы и объяснения

2013-04-04T17:49:33+00:00

1) у = 3x - 7

    2x + 3y = 1

 

y = 3x - 7

2x + 3(3x - 7) = 1

 

y = 3x - 7

2x + 9x - 21 - 1 = 0

 

y = 3x - 7

11x = 22  

 

y = 3x - 7

x = 22/11 = 2

 

y = 3*2 - 7 = -1

x = 2

 

Ответ: x=2, y=-1

 

2) 6x +6y + у -8 - 2x +2y = 0

     5y - 5x - 5 + y - 3x - 3y = 0

 

     4x + 9y - 8 = 0

     -8x + 3y - 5 = 0

 

     x = (8 - 9y)/4

     8x - 3y +5 = 0

 

     x = (8 - 9y)/4

     8* ((8 - 9y)/4) - 3y +5 =0

 

     x = (8 - 9y)/4

     16 - 18y - 3y +5 = 0

 

     x = (8 - 9y)/4

     21y = 21

 

     x = (8 - 9y)/4

     y = 1

 

     y=1

     x = (8 - 9*1)/4 = - 0,25     - ответ